Emerging roles of mesenchymal stem cell-derived exosomes in gastrointestinal cancers - Wang, Naijian; Pei, Bing; Yuan, Xinyi; Yi, Chengxue; Wiredu Ocansey, Dickson Kofi; Qian, Hua; Mao, Fei (Frontiers in Bioengineering and Biotechnology, 2022)
Gastrointestinal tumours are the most common solid tumours, with a poor prognosis and remain a major challenge in cancer treatment. Mesenchymal stem cells (MSC) are multipotent stromal cells with the potential to differentiate into multiple cell types. Several studies have shown that MSC-derived exosomes have become essential regulators of intercellular communication in a variety of physiological and pathological processes. Notably, MSC-derived exosomes support or inhibit tumour progression in different cancers through the delivery of proteins, RNA, DNA, and bioactive lipids. Herein, we summarise current advances in MSC-derived exosomes in cancer research, with particular reference to their role in gastrointestinal tumour development. MSC-derived exosomes are expected to be a novel potential strategy for the treatment of gastrointestinal cancers.